Assessment of auditory threshold using Multiple Magnitude-Squared Coherence and amplitude modulated tones monaural stimulation around 40 Hz. (June 2018) - Silva, Glaucia de Morais; Antunes, Felipe; Henrique, Catherine Salvador; Felix, Leonardo Bonato
Highlights: We acquired EEG during monaural AM stimulation in the 40 Hz range. We developed a new computational procedure to estimate auditory thresholds This procedure is performed without feedback from volunteers. The procedure applies Multiple Magnitude-Squared Coherence and multichannel EEG. The results show a reliable estimate of auditory levels, reducing detection time. Abstract: Background and Objective: The use of objective detection techniques applied to the auditory steady-state responses (ASSRs) for the assessment of auditory thresholds has been investigated over the years. The idea consists in setting up the audiometric profile without subjective inference from patients and evaluators. The challenge encountered is to reduce the detection time of auditory thresholds reaching high correlation coefficients between the objective and the conventional thresholds, as well as reducing difference between thresholds. Methods: This paper evaluated the use of the Multiple Magnitude-Squared Coherence (MMSC) in Auditory Steady-State Responses (ASSRs) evoked by amplitude modulated tones around 40 Hz, attaining objective audiograms, which were, later, compared to conventional audiograms. It was proposed an analysis of the electroencephalogram signals of ten subjects, monaurally stimulated, in the intensities 15, 20, 25, 30, 40 and 50 dB SPL, for carrier frequencies of 0.5, 1, 2 and 4 kHz. After the detection protocol parameters variation, two detectors were selected according to behavioral thresholds. Results: The method of this study resulted in a Maximum detector with correlation coefficient r = 0.9262, mean difference between the objective and behavioral thresholds of 6.44 dB SPL, average detection time per ear of 49.96 min and per stimulus of 2.08 min. Meanwhile, the Fast detector presented coefficient r = 0.8401, mean difference of 6.81 dB SPL, average detection time of 28.20 min per ear and 1.18 per stimulus. Conclusions: The results of this study indicate that the MMSC use in the auditory responses detection might provide a reliable and efficient estimation of auditory thresholds.